Corporate Governance, Audit Quality, Firm Size and Leverage: Their Effect on Earnings Management - Andry Priharta,; Gani, Nur Asni; Jaharuddin, Jaharuddin; Utama, Rony Edward (Technium Social Sciences Journal, 2022)
The objectives of this research are to estimate and analyze the effect of corporate governance, audit quality, firm size, and leverage on earnings management, either partially or simultaneously. The research method used is panel data regression analysis. Purposive sampling approach was used, choosing six companies that consistently participated in the Corporate Governance Perception Index (CGPI) program from 2014 to 2019 and are listed on the Indonesia Stock Exchange. The results show that CGPI has a significant negative effect, audit quality has no significant effect, firm size has a significant negative effect, leverage has a significant positive effect on earnings management. CGPI, audit quality, firm size, and leverage simultaneously have a significant effect on earnings management with a coefficient of determination (R2) of 0.7936, indicating that all independent variables can explain variations in earnings management by 79.36%, while the remaining 20. 64% is explained by other factors not to be included in the model.